Beyond Personal Identity. Dogen, Nishida and a Phenomenology of No-Self. Gereon Kopf. - Cestari, Matteo (Buddhist Studies Review, 2002)
Beyond Personal Identity. Dogen, Nishida and a Phenomenology of No-Self. Gereon Kopf. Curzon Press, Richmond (Surrey) 2001. xx, 298 pp. 40.00. ISBN 0-7007-1217-8.